The Spinner in the Poetry of Isaac Lebusch Peretz (An analytical study) (Journal of the College of Basic Education, 2023)
Among the many changes that took place in the fields of Hebrew poetry in the late nineteenth century, relatively far-reaching transformations emerged, in the concept of the art of finesse of poetry, as well as in the way of its concrete formulation and realistic formation. Emotional poems in general and love poems and spinning in particular, and they were brief and wise compared to the average poetry in the Sakala period, as well as with that essential importance in terms of contemplative research, as it succeeded in finding the semantic meaning by constructing the meanings of the words of poetry or what is called the science of semantics.When examining the critical trends that dealt with the poetic collection of Isaac Lebusch Bernice, it becomes clear that they fluctuate between underestimating them altogether and evaluating them positively, and this evaluation is generally impressionistic and somewhat conservative. ).This collection of poetry included poems and poems divided into two groups in terms of the main idea (the function). Both groups describe (the sick soul) and (I am the poet) all the poems in which a mood appears clearly and clearly for a mood that is called in the language of the poetic world (the sick, the sinkhole of love) or (the depressed). The poet describes here that near the beloved, he feels her magical advantages (her eyes), the manifestation of worry and anguish, and the overhanging shadows, so the poet contemplates her permanent presence and her eternal presence, and looks forward to achieving this. She changes (her masks) and the lover cannot ascertain her true image, and sometimes a clear hostile attitude appears through her, that she (the beloved) rebels and makes others sympathize with her and deceives those who court her with cruel deception, and the lover continues (worshiping her) in most cases hoping for a look of sympathy and fairness from her.Such ideas appeared in the transitional period among other writers in different proportions, but only the poetry of Berenice, according to my point of view, lies in its moral composition.There is no doubt that these anthologies of poetry do not correspond to the same degree in terms of their complexity, quality, and composition, and thus the influence of the Haskalah appears, in other words, an influential rhetorical situation composed of indexed paragraphs on a well-known classified basis, such as (with all the buds), (secrets of the stars and the heavens), (a bird without wings) or gradually defining such as: (your eyebrow that advises heavenly) and other monologues in the chapter (the Tamarah) (the chapter of the Mishna and the Talmud), and yet there is no denying that the relatively numerous verses in which a departure from the old standard appear and make an important beginning in the direction of A dynamic semantic structure in the spirit of (the changing form of poetry) or (the opposite poem model) it is possible to put a hierarchical scale between these two poles to benefit from it in an attempt to determine the value and importance of the poetic group in the development of Hebrew poetry in the Renaissance.